An Exploration of Inclusive Education Policies Aimed at Students with Disabilities vs. the Panorama of EFL Scenarios in Colombia (2017)
This article reflects upon the policies that regulate inclusive education in Colombia for students with disabilities and contrasts it with the reality of EFL teaching/learning nowadays. The concept of inclusion has gained interest among government officials and scholars in recent decades; as a result, much inclusivity legislation has been created to guarantee access for disabled students in mainstream schools. However, there are not clear procedures and adequate scenarios to address foreign language education in Colombia for this population, resulting in more exclusion, discrimination and lack of opportunities for disabled learners.